Economic growth and demographic transition in the third world nations : a chaos and complexity theory perspective - Ercetin, Sefika Sule; Ray, Nilanjan, 1984-; Sen, Saurabh, 1978- (Palm bay, Florida: Apple Academic Press, 2019)
"This volume presents a new perspective on demographic transition, economic growth, and national development via exploration of the Third World economies. It provides a multidimensional approach to the close relationship between the concept of the chaos and complexity theory and provides a deliberate glance into the plight of policy formulation for demographic transition, economic growth, and development and Third World countries. The volume discusses the efficiency of good strategies and practices and their impact on business growth and economic growth, depending on the depth and diversity of infrastructure sector in particular and overall socioeconomic development in general"--
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- Developing countries; Demographic transition -- Developing countries; Infrastructure (Economics) -- Developing countries; Developing countries -- Economic policy; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / International / Economics; BUSINESS & ECONOMICS / Economics / Theory